Respon Pengemudi Ojek Online terhadap Gerakan Stop Tot tot wuk wuk sebagai Wujud Kesadaran Toleransi di Jalan Raya (Studi Kasus di Kota Surabaya) - Nur Azizah Rahayu Ningsih; Nur Chamidah; Sasmia Desinta Wulandari; Siti Maizul Habibah (Jurnal Ilmu Sosial dan Humaniora, 2025)
The roadway, as a shared public space, requires all users to develop awareness, tolerance, and adherence to traffic regulations. The response of online motorcycle taxi drivers to the stop tot tot wuk wuk movement represents a form of articulated tolerance awareness in road interactions, particularly within the socio-traffic context of Surabaya City. This study employs a descriptive qualitative approach with a case study design. Data were collected through semi-structured interviews and non-participant observations. The analysis process utilized the Miles and Huberman model, while data validity was ensured through technique triangulation. The findings indicate that the stop tot tot wuk wuk movement is perceived by drivers as a critique of the improper use of sirens, which often generates psychological pressure, discomfort, and unequal relations among road users. Although online motorcycle taxi drivers frequently choose to yield for the sake of safety and traffic flow, they also experience ethical imbalance in the use of public road space. This phenomenon illustrates that tolerance on the road has not yet matured as a shared moral consciousness. Thus, the movement serves not only as an expression of social critique but also as a reflective moment to strengthen the values of tolerance and traffic ethics.